Conceptual frameworks for the workplace change adoption process: elements integration from decision making and learning cycle process. Issue 9 (2nd September 2018) - Radin Umar, Radin Zaid; Sommerich, Carolyn M.; Lavender, Steve A.; Sanders, Elizabeth; Evans, Kevin D.
Abstract: Sound workplace ergonomics and safety-related interventions may be resisted by employees, and this may be detrimental to multiple stakeholders. Understanding fundamental aspects of decision-making, behavioural change, and learning cycles may provide insights into pathways influencing employees' acceptance of interventions. This manuscript reviews published literature on thinking processes and other topics relevant to decision making and incorporates the findings into two new conceptual frameworks of the workplace change adoption process. Such frameworks are useful for thinking about adoption in different ways and testing changes to traditional intervention implementation processes. Moving forward, it is recommended that future research focuses on systematic exploration of implementation process activities that integrate principles from the research literature on sense-making, decision-making, and learning processes. Such exploration may provide the groundwork for development of specific implementation strategies that are theoretically grounded and provide a revised understanding of how successful intervention adoption processes work. Practitioner summary: Adoption and acceptance of workplace changes may be facilitated through sound implementation strategies. This manuscript explores several principles of sense-making and decision-making processes that can potentially be used by industrial practitioners to inform the design and development of implementation strategies for interventions that improve workplace ergonomics and safety. Abbreviations: Musculoskeletal Disorders (MSDs); National Institute for Occupational Safety and Health (NIOSH); National Occupational Research Agenda (NORA); Health and Safety Executive (HSE)